2011
DOI: 10.5125/jkaoms.2011.37.6.510
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the temporomandibular joint: a report of three cases

Abstract: (J Korean Assoc Oral Maxillofac Surg 2011;37:510-4) An intracapsular and pericapsular infection of the temporomandibular joint (TMJ) is rare. The invasion of bacteria into the joint space can occur through several routes. Among them, hematogenous spread is most common. This report describes three cases of abscess formation in the TMJ (intracapsular and pericapsular infection). The patients were treated with supportive care and surgical intervention (incision and drainage) under hospitalization, and their sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Both patients were ultimately diagnosed with MSA. Kim et al 9 reported three cases of MSA that did not have an odontogenic origin. Of these, one patient had no specific etiology, one had an upper respiratory infection, and the other had experienced trauma to the chin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both patients were ultimately diagnosed with MSA. Kim et al 9 reported three cases of MSA that did not have an odontogenic origin. Of these, one patient had no specific etiology, one had an upper respiratory infection, and the other had experienced trauma to the chin.…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic causes include periodontitis, pericoronitis, dental caries, suppurative pulpitis, and post-tooth extraction infection 3 , 4 . In addition to these common causes, sinusitis 5 , sinus fracture 6 , posttraumatic osteomyelitis of the maxilla 7 , temporomandibular arthroscopy 8 , and trauma 3 , 9 can also cause MSA 4 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a very complex system under permanent and dynamic changes throughout life. Infections of the TMJ in both intracapsular and pericapsular courses are rare diseases [100]. The predisposing factors for contributing to TMJ infections are divided into local factors, such as blunt trauma, history of joint diseases and burn, and systemic factors including autoimmune disease and overconsumption of medicines with special reference to steroids [57,101,102].…”
Section: Periprosthetic Joint Infectionsmentioning
confidence: 99%
“…[ 2 ] Failure to promptly treat septic arthritis of the TMJ may result in joint dysfunction, fibrosis, and alkylosis. [ 3 ] This report describes a case of TMJ septic arthritis in a healthy 24-year-old male that was promptly treated and resolved without any complications.…”
Section: Introductionmentioning
confidence: 99%